Colorectal Cancer Screening: Physicians’ Knowledge of Risk Assessment and Guidelines, Practice, and Description of Barriers and Facilitators - Maida J Sewitch; Pascal Burtin; Martin Dawes; Mark Yaffe; Linda Snell; Mark Roper; Patrizia Zanelli; Alan Pavilanis (Canadian Journal of Gastroenterology)
BACKGROUND: Physician nonadherence to colorectal cancer (CRC) screening recommendations contributes to underuse of screening.